2021
DOI: 10.1172/jci.insight.147929
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-like signature in ovarian cancer minimal residual disease identifies metabolic vulnerabilities of tumor initiating cells

Abstract: Similar to tumor initiating cells (TICs), minimal residual disease (MRD) is capable of re-initiating tumors and causing recurrence. However, the molecular characteristics of solid tumor MRD cells and drivers of their survival have remained elusive. Here we performed dense multi-region transcriptomics analysis of paired biopsies from 17 ovarian cancer patients before and after chemotherapy. We reveal that while MRD cells share important molecular signatures with TICs, they are also characterized by an adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Effective ovarian cancer therapy requires the eradication of CSCs [1,20], which are thought to drive tumor initiation, metastasis, and therapy resistance [1,21,26]. Our previous study revealed that the cell surface proteins CD44v6 and EpCAM play crucial roles in regulating ovarian cancer stemness, promoting metastasis, and enhancing chemotherapy resistance [20,23,24,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective ovarian cancer therapy requires the eradication of CSCs [1,20], which are thought to drive tumor initiation, metastasis, and therapy resistance [1,21,26]. Our previous study revealed that the cell surface proteins CD44v6 and EpCAM play crucial roles in regulating ovarian cancer stemness, promoting metastasis, and enhancing chemotherapy resistance [20,23,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that the bulk of cancer cells are generated by rare populations of selfrenewing, multipotent tumor-initiating cells, conceptually termed "cancer stem cells" (CSCs) [20,21]. CSCs are inherently responsible for metastasis and therapy resistance [1,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a transcriptomic study of single cell-derived spheroids from ovarian cancer ascites has shown that although 2D monolayers support proliferation and tumour growth cascades, 3D spheroids additionally capture aspects of cholesterol and lipid metabolism, which are features of metastatic disease 9 . These pathways are implicated in the lipid signature we observed in ovarian cancer MRD 4 ; thus, in this context, 3D models are essential for drug discovery.…”
Section: Introductionmentioning
confidence: 92%
“…In a previous work we described how MRD cells show distinctive features such as the upregulation of cancer stem cell markers and genes involved in lipid metabolism, and a more pronounced mesenchymal profile 4 . We also developed an MRD 2D in vitro model where treatmentnaïve cancer cells were exposed to carboplatin concentrations to achieve >90% cell killing; the surviving cells recapitulated some of the features of MRD (such as upregulation of lipid metabolism), but lacked the complexity of multicellularity and three dimensionality.…”
Section: D Microtumours As a Superior Model Of Ovarian Cancer Mrdmentioning
confidence: 99%
See 1 more Smart Citation